The Bell Jar : Troubles dans le genre - Angélique THOMINE-RAPP (E-REA)
This article revisits the categorical vagueness of The Bell Jar, Sylvia Plath’s only completed novel. At times referred to as an autobiographical or semi-autobiographical novel and at other times as a non-fiction novel, her work sparks debate on how one might categorize its genre. Published in 1963 in the United Kingdom under the pen name Victoria Lucas right before Plath’s early death, the novel, set in the 1950s, follows the protagonist Esther Greenwood, an American student who, for many, closely resembles Plath. The blurred line between fiction and non-fiction genres was the central question during the 1986 libel lawsuit against the film crew of the 1979 film adaptation of The Bell Jar. Jane Anderson, who supposedly inspired the character Joan Gilling in The Bell Jar, sued members of the film crew and Ted Hughes, who held all rights to the novel. This article analyzes how this lawsuit contributed to the confusion between Sylvia Plath and The Bell Jar’s narrator and deconstructs how the resistance of many to accept The Bell Jar into a literary genre is due in large part to the myth surrounding Plath as an author and the public fascination about her private life, which obscured the importance of the novel’s social aspects as well as its critical look into American society.